Staged reconstruction of large skull defects with soft tissue infection after craniectomy using free flap and cranioplasty with a custom-made titanium mesh constructed by 3D-CT-guided 3D printing technology: Two case reports. Issue 6 (February 2019) - Kim, Seong Hwan; Lee, Seong Joo; Lee, Jun Won; Jeong, Hii Sun; Suh, In Suck
Abstract: Rationale: A craniectomy, which results in a large skull defect, is performed to decrease the intracranial pressure under conditions such as intracranial hemorrhage and ischemic stroke. When the patient's condition is stabilized, autologous cranioplasty using the bone flap previously removed in the craniectomy is performed. Bone flap infection after the autologous cranioplasty is not uncommon and is difficult to treat. After the infection is controlled, cranioplasty is needed to improve the head deformity and neurologic function. Cranioplasty with a titanium mesh can result in aesthetic improvement and a low infection rate. Using 3-dimensional computed tomography (3D-CT) and 3D printing, titanium mesh is manufactured to fit perfectly on the patient's skull defect. Patient concerns: Two patients with large skull defects in the right temple area due to previous craniectomy were referred to our department for reconstruction. They had histories of recurrent infections at the operation site even after removal of the autologous bone flap that had been used for the cranioplasty. Diagnosis: Preoperative computed tomography (CT) showed 12×16 cm and 8×8.3 cm skull defect on right temporal area, respectively. Interventions and outcome: The infection was controlled by well-vascularized free flap coverage. After the surgery, cranioplasty with custom-made titanium mesh was performed to improve the aesthetic and functional problems of the patients. The contour of the temporal area was symmetric. The patients were satisfied with the results. Lessons: Staged reconstruction of large skull defects with soft tissue infection after craniectomy using free flap followed by cranioplasty with titanium mesh on can lead to safe, aesthetic, and satisfactory result.